The use of laser lead extraction sheath in the presence of supra-cardiac occlusion of the central veins for cardiac implantable electronic device lead upgrade or revision - Maisary, Sameer al-; Romano, Gabriele; Karck, Matthias; De Simone, Raffaele; Kremer, Jamila (PLOS ONE, 2021)
Background The implantation of cardiac implantable electronic devices (CIED) has increased in the last decades with improvement in the quality of life of patients with cardiac rhythm disorders. The presence of bilateral subclavian, innominate or superior vena cava obstruction is a major limitation to device revision and/or upgrade. Methods and material This is retrospective study of patients who underwent laser-assisted lead extraction (LLE) (GlideLight laser sheath, Spectranetics Corporation, Colorado Springs, USA) with lead revision or upgrade using the laser sheath as a guide rail. Patients with known occlusion, severe stenosis or functional obstruction of the venous access vessels with indwelling leads were included in this study. Results 106 patients underwent percutaneous LLE with lead revision and/or upgrade. Preoperative known complete occlusion or severe stenosis of access veins was present in 23 patients (21.5%). More patients with implantable cardioverter-defibrillator (ICD) underwent LLE (64.1%) than patients with CRT-Ds (24.5%) and pacemaker patients (11.3%). In total 172 leads were extracted: 79 (45.9%) single-coil defibrillator leads, 35 (20.3%) dual-coil defibrillator leads, 31 (18.0%) right atrial leads, 24 (13.9%) right ventricular leads and three (1.7%) malfunctional coronary sinus left ventricular pacing leads. The mean age of leads was 99.2±65.6 months. The implantation of new leads after crossing the venous stenosis/obstruction was successful in 98 (92.4%) cases. Postoperative complications were pocket hematoma in two cases and wound infection in one case. No peri-operative and no immediate postoperative death was recorded. One intraoperative superior vena cava tear was treated by immediate thoracotomy and surgical repair. Conclusion In a single-center study on LLE in the presence of supra-cardiac occlusion of the central veins for CIED lead upgrade and revision we could demonstrate a low procedural complication rate with no procedural deaths. Most of the leads could be completely extracted to revise or upgrade the system. Our study showed a low complication rate, with acceptable mortality rates.